Correlation Between the Tahfiz Al-Qur'an Program and Students' Emotional Intelligence at MAS Muallimin UNIVA Medan - Dedi Masri; Pandu Prabowo Warsodirejo; Surya Aymanda Nababan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study will investigate this relationship between the tahfiz and the students' emotional intelligence. Quantitative research and correlational methodology are used in this study. The research population consists of 97 students from Madrasah Aliyah Swasta Muallimin UNIVA Medan. Cluster random sampling was employed as the sampling method in this research. A questionnaire was used as the data collection method. The study data were examined using the t-test statistical method, the coefficient of determination test, and the Pearson product moment correlation. According to the study's findings, students at MAS Muallimin Univa Medan's emotional intelligence is significantly influenced by the tahfiz students. This is supported by the person correlation value of 0.620 and the sig value of 0.000 < 0.05. The Tahfidz Al-Qur'an program makes a 38% contribution to the emotional intelligence of pupils. The results of the t test show that tcount > ttable with Sig = 0.000 < 0.05). Using the formula dk = n-k = 95, the tcount is 7,712 and the ttable value is 1,985, with a significant level of 5%. The results of the study show a strong relationship between students' emotional intelligence and the Tahfidz Al-Qur'an curriculum. These findings are valuable for educators in developing impactful programs that enhance the overall quality of graduates in terms of intellectual capabilities, attitudes, and skills. Additionally, stakeholders can leverage the research to inform education policies and strive for outstanding graduates.